Technological Innovation Adoption Among Swedish Healthcare Professionals : A Contingency Technology Adoption Framework - Madanaguli, Arun; Parida, Vinit; Oghazi, Pejvak; Tran, Phan Kiet (IEEE, 2023)
Technological innovation adoption by healthcare professionals directly impacts enhanced patient care and overall community well-being. However, the perspective of healthcare professionals in evaluating and adopting these technological innovations should be addressed. Drawing on innovation adoption and resistance theories, in this article, we aim to capture their perceptions of the barriers they face and the adoption behaviors they express through a technology adoption contingency framework. The qualitative investigation on Swedish healthcare professionals shows that healthcare innovations are multistakeholder systems where the healthcare-professional's perception of multiple individual, organizational, and administrative barriers causes hesitancy in adopting technologies. However, hesitancy does not always lead to complete resistance; sometimes, it can lead to partial or complete adoption of the technology, contingent on the severity of the barriers and their interrelationship. The findings, summarized in a contingency framework for evaluating barriers to adoption and hesitancy behaviors, highlight the importance of individual perceptions in the adoption and success of complex healthcare innovations. They show why empowering adopters to choose how and when to use the innovation can be a powerful tool in reducing hesitancy.
Keywords: Innovation resistance; surgeon behavior; surgical innovations; technology adoption; fi=Strateginen johtaminen|en=Strategic Management|